FAKTOR- FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN DIARE PADA BALITA DI WILAYAH KERJA PUSKESMAS PUJUD - Septi Akhwi Fanni; Erwin Erwin; Riri Novayelinda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
Diarrhea is defined by loss of fluids and electrolytes in the form of watery or liquid stools more than 3 times a day which may be accompanied by vomiting or stools and blood. This study aims to determine the factors associated with the incidence of diarrhea in children under five in the working area of Pujud Public Health Center. This study used a correlation research design with a cross sectional approach with a total sample of 78 respondents who had children under five (12-48) months old who met the inclusion criteria. The measuring instrument used is a questionnaire. The majority of full adult mothers (26-60 years) were (83.3%), the majority of toddlers (12-36 months) were (84.6%), the majority of elementary school education (34.6%), the majority of housewives work as much as (47.4%), the majority of diarrhea events occur as much as (60.3%), the majority of knowledge is sufficient as much as (74.4%), the majority of the habit of washing hands sometimes as much as (71.8%) , the majority of waste disposal is not good as much as (52.6%), the majority of knowledge with the incidence of diarrhea in toddlers is sufficient (75.9%), the majority of hand washing habits with the incidence of diarrhea in toddlers are sometimes as much as (69.6%), the majority of waste disposal with diarrhea in toddlers is not good as much as (87.8%). There is a relationship between knowledge and the incidence of diarrhea in toddlers at the Pujud Health Center, there is a relationship between hand washing habits and the incidence of diarrhea in toddlers at the Pujud Health Center, there is a relationship between waste disposal and the incidence of diarrhea in toddlers at the Pujud Health Center. It is expected that mothers always pay attention to environmental hygiene, wash their hands with soap, running water and always check their toddler's health regularly at the Puskesmas. Keywords: Diarrhea Incidence;Toddler